Research and application of digital measure management and control technology for characteristic low-efficiency gas wells in Gas Field A - Hao-Yang Li; Wen-hai Ma; Jun-liang Li; Cheng-gang Jiang; Pin-gang Ma; De-song Yao; Ming-xi Feng; Shao-xing Gu (PLoS ONE, 2025)
Gas Field A has entered the middle and late stages of development, with the number of low-efficiency wells increasing year by year. In the Songliao old area, extreme cold weather (-40°C) has led to 45% of gas wells experiencing freeze-offs. In the Sichuan-Chongqing exploration area, high formation water volume and salinity (35 × 10 4 mg/L) have resulted in 44% of wells suffering from liquid loading. The annual demand for thawing and foam drainage measures reaches 3,000 well interventions. The large workload and high costs of maintenance make it difficult to ensure the timing and frequency of interventions, affecting the gas recovery efficiency. By establishing an integrated analysis and remote monitoring platform that combines “condition diagnosis, measure adjustment, and remote monitoring,” the use of “freeze-off prediction + precise chemical injection” has improved the opening rate of freeze-off wells. The application of “optimized foam drainage injection parameters” ensures the stable production of liquid-loaded wells. The implementation of this technology is expected to generate over 20 million yuan in benefits and enhance the analysis, decision-making, and control capabilities of gas production processes under extreme weather and production conditions.